2005
DOI: 10.1007/s10620-005-3008-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Nasogastric Intubation for Gastrointestinal Bleeding After Myocardial Infarction: An Analysis of 125 Patients at Two Tertiary Cardiac Referral Hospitals

Abstract: Our purpose was to analyze risks versus benefits of nasogastric (NG) intubation for gastrointestinal (GI) bleeding performed soon after myocardial infarction (MI). While NG intubation and aspiration is relatively safe, clinically beneficial, and routinely performed in the general population for recent GI bleeding, its safety after MI is unstudied and unknown. In addition to the usual complications of NG tubes, patients status post-MI may be particularly susceptible to myocardial ischemia or cardiac arrhythmias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The bright red blood suggests active bleeding, while the dark red blood suggests recent bleeding. The continuous aspiration of bright red blood suggests severe active bleeding, associated with a higher rate of evidence of active bleeding and other endoscopic stigmas of recent hemorrhaging while performing an emergency UGE, as compared to a dark red aspiration or without the presence of blood [18].…”
Section: Nasogastric Cathetermentioning
confidence: 97%
See 1 more Smart Citation
“…The bright red blood suggests active bleeding, while the dark red blood suggests recent bleeding. The continuous aspiration of bright red blood suggests severe active bleeding, associated with a higher rate of evidence of active bleeding and other endoscopic stigmas of recent hemorrhaging while performing an emergency UGE, as compared to a dark red aspiration or without the presence of blood [18].…”
Section: Nasogastric Cathetermentioning
confidence: 97%
“…The erosions are recognized as being multiple, collinear, equidistant, rounded, and relatively uniform, as well as being in the same stage of evolution [11]. In a review of 152 nasogastric catheterisms in patients with upper gastrointestinal bleeding, considering that of these, 125 had suffered an acute myocardial infarction within a period of 30 days prior to the procedure, only two (1.3%) cases presented clinically significant complications, including one case of nosebleeds and another of gastric erosion induced by the tube, both of which were treated with a blood transfusion (red blood cell concentrates), evolving with no clinical sequelae [18]. The risk of nosebleeds is reduced with the use of a correct technique, when introduced softly, with lubrification of the end of the tube, with cooperation from the patient, suspension of venous heparine therapy four hours prior to the introduction of the catheter, and avoiding the insertion when a coagulopathy is detected.…”
Section: Nasogastric Cathetermentioning
confidence: 99%
“…After the exclusions, we based our review on three studies. 15,17,18 We did not find any systematic reviews or meta-analyses on this subject. All three studies included in our review had retrospective designs.…”
Section: Searchmentioning
confidence: 92%
“…We identified four observational studies that met our selection criteria. [15][16][17][18] We excluded one study 16 because the results of the reference standard test (EGD) was not reported in patients with negative nasogastric aspirates. Also, 18% of patients with positive nasogastric aspirates did not receive EGD.…”
Section: Searchmentioning
confidence: 99%
See 1 more Smart Citation